Language and Automata Theory and Applications 8th International Conference, LATA 2014, Madrid, Spain, March 10-14, 2014, Proceedings - Dediu, Adrian-Horia; Martín-Vide, Carlos; Sierra-Rodríguez, José-Luis; Truthe, Bianca (Theoretical Computer Science and General Issues, 2014)
This book constitutes the refereed proceedings of the 8th International Conference on Language and Automata Theory and Applications, LATA 2014, held in Madrid, Spain in March 2014. The 45 revised full papers presented together with 4 invited talks were carefully reviewed and selected from 116 submissions. The papers cover the following topics: algebraic language theory; algorithms on automata and words; automata and logic; automata for system analysis and program verification; automata, concurrency and Petri nets; automatic structures; combinatorics on words; computability; computational complexity; descriptional complexity; DNA and other models of bio-inspired computing; foundations of finite state technology; foundations of XML; grammars (Chomsky hierarchy, contextual, unification, categorial, etc.); grammatical inference and algorithmic learning; graphs and graph transformation; language varieties and semigroups; parsing; patterns; quantum, chemical and optical computing; semantics; string and combinatorial issues in computational biology and bioinformatics; string processing algorithms; symbolic dynamics; term rewriting; transducers; trees, tree languages and tree automata; weighted automata.